An environmental and economic assessment of bioplastic from urban biowaste. The example of polyhydroxyalkanoate. (May 2021) - Andreasi Bassi, Susanna; Boldrin, Alessio; Frenna, Giammarco; Astrup, Thomas F.
Highlights: Polyhydroxyalkanoates production from food waste and sewage sludge was investigated. Life cycle assessment (LCA) and societal life cycle costing (LCC) were applied. Polyhydroxyalkanoates from urban biowaste outperform polyurethane. Possible improvements in the production process chain are identified. Local conditions are critical for the polyhydroxyalkanoate performance. Abstract: Bio-based and biodegradable plastics promise considerable reductions in our dependency on fossil fuels and in the environmental impacts of plastic waste. This study quantifies the environmental and economic consequences of diverting municipal food waste and wastewater sewage sludge from traditional management to the biorefinery-based production of polyhydroxyalkanoates (PHA) in five geographical regions. The results show that PHA can outperform fossil polyurethane and PHA from first-generation biomass (sugarcane and maize) with respect to both environmental impacts and societal costs (four times lower impacts and eight times lower costs than polyurethane). To outperform other fossil polymers like low-density polyethylene (LDPE), biorefinery performance should be improved further by more efficient utilization of sodium hypochlorite during PHA extraction, minimization of methane leakage in biogas facilities, upgrading of biogas to biomethane, and more effective handling of the liquid fraction from digestate dewatering.